Noncoding SNPs influence a distinct phase of Polycomb silencing to destabilize long-term epigenetic memory at Arabidopsis FLC - Qüesta, Julia I. (Genes Dev, 2020)
In Arabidopsis thaliana, the cold-induced epigenetic regulation of FLOWERING LOCUS C (FLC) involves distinct phases of Polycomb repressive complex 2 (PRC2) silencing. During cold, a PHD–PRC2 complex metastably and digitally nucleates H3K27me3 within FLC. On return to warm, PHD–PRC2 spreads across the locus delivering H3K27me3 to maintain long-term silencing. Here, we studied natural variation in this process in Arabidopsis accessions, exploring Lov-1, which shows FLC reactivation on return to warm, a feature characteristic of FLC in perennial Brassicaceae. This analysis identifies an additional phase in this Polycomb silencing mechanism downstream from H3K27me3 spreading. In this long-term silencing (perpetuated) phase, the PHD proteins are lost from the nucleation region and silencing is likely maintained by the read-write feedbacks associated with H3K27me3. A combination of noncoding SNPs in the nucleation region mediates instability in this long-term silencing phase with the result that Lov-1 FLC frequently digitally reactivates in individual cells, with a probability that diminishes with increasing cold duration. We propose that this decrease in reactivation probability is due to reduced DNA replication after flowering. Overall, this work defines an additional phase in the Polycomb mechanism instrumental in natural variation of silencing, and provides avenues to dissect broader evolutionary changes at FLC.